2022
DOI: 10.1177/14644207221116032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and analysis of sound-absorbing properties of waste tea leaf fiber as fillers in pineapple leaf/glass fiber-reinforced composites

Abstract: To control the noise pollution through sound absorption, the development of natural fiber-reinforced hybrid composites (NFRHCs) using waste tea leaf fibers (WTLFs) and pineapple leaf fibers as reinforcing materials with epoxy matrix will act as an initial step to address this issue. Also, a minimal additional reinforcement of glass fibers was added for achieving mechanical strength too. The fabricated samples underwent a sound absorption test for assessing their capability of absorbing unwanted noise. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In this regard, predicting the behavior of polyester-glass fiber composites under tensile loading becomes paramount for designing durable structures. Factors such as the content and length of glass fibers and the composite plates' thickness significantly influence their mechanical performance (Akpinar;Akpinar, 2023;Chavan et al, 2023;Gokulkumar et al, 2022;Moustapha Sarr;Kosaka, 2023). This experimental investigation focuses on the prediction of durability for polyester-glass fiber composites under tensile loading.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, predicting the behavior of polyester-glass fiber composites under tensile loading becomes paramount for designing durable structures. Factors such as the content and length of glass fibers and the composite plates' thickness significantly influence their mechanical performance (Akpinar;Akpinar, 2023;Chavan et al, 2023;Gokulkumar et al, 2022;Moustapha Sarr;Kosaka, 2023). This experimental investigation focuses on the prediction of durability for polyester-glass fiber composites under tensile loading.…”
Section: Introductionmentioning
confidence: 99%
“…Rafique et al 24 discussed the SA properties of microperforated samples with spider web-shaped cavities using the impedance tube technique. Gokulkumar et al 25 analyzed the SA properties of tea and pineapple leaf fibers composites. Their study revealed that the effect of thickness, fiber density, and weight fraction of hybrid composites improves the SAC.…”
Section: Introductionmentioning
confidence: 99%